2005
DOI: 10.1021/ja055752d
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Asymmetric, “Interrupted” Feist−Bénary Reactions

Abstract: Pyrimidine derivatives of the cinchona alkaloids function as excellent asymmetric catalysts for the "Interrupted" Feist-Bénary Reaction. This reaction produces highly substituted hydroxydihydrofurans from simple starting materials under mild conditions. The asymmetric reaction gives high enantioselectivities with unsubstituted bromoketones, and high enantio- and diastereoselectivities with substituted substrates. Mechanistic experiments suggest that the hydrobromide salt of the alkaloid derivative is the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 10 publications
0
75
0
3
Order By: Relevance
“…5 (DHQD) 2 PHAL 1d and (DHQ) 2 PHAL 1c were the optimal catalysts in the reaction of ethyl bromopyruvate and the phenyl-substituted bromoketoester, respectively. Further investigations are planned to provide additional information with regard to the scope and precise mechanism of the reaction.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…5 (DHQD) 2 PHAL 1d and (DHQ) 2 PHAL 1c were the optimal catalysts in the reaction of ethyl bromopyruvate and the phenyl-substituted bromoketoester, respectively. Further investigations are planned to provide additional information with regard to the scope and precise mechanism of the reaction.…”
Section: Resultsmentioning
confidence: 97%
“…3,4 Calter et al first reported the application of cinchona alkaloid catalysts in IFB reactions. 5 They coupled different substituted pyrimidinyls with cinchona alkaloids to afford a series of catalysts and found that diphenylpyrimidinyl derivatives gave optimal asymmetric induction. Interestingly, slight changes to a substituent of the catalysts or different cinchona alkaloids significantly affected the enantiomeric purity of products (14-98%).…”
Section: Introductionmentioning
confidence: 99%
“…The IFB reaction is important for an easy access to substituted dihydrofurans which are constituents of many natural products arising from plants and marine organisms with promising biological activities. However, only a limited number of methods are available for FB and IFB reactions [114][115]. The basic ionic liquid, 1-butyl-3-methylimidazolium hydroxide promoted the interrupted Feist-Benary reaction at room temperature under organic solvent-free conditions to produce a variety of substituted hydroxydihydrofurans.…”
Section: Feist-benary Reactionmentioning
confidence: 99%
“…They proposed that the protonated cinchona alkaloid would perform as a Brønsted acid to form hydrogen-bonding interaction with a-ketoester moiety, rendering it more electrophilic toward attack by either the enol or enolate of cyclohexandione. Then intramolecular alkylation would afford the formal [3 þ 2] cycloadduct (Scheme 10.12) [16].…”
Section: Asymmetric Cycloadditions Catalyzed By Quinuclidine Tertiarymentioning
confidence: 99%
“…A variety of azomethine imines reacted directly with cyclic enones, forming the desired tricyclic products in good yield (72-99%) and ee (86-95%), while having excellent diastereoselectivity (all >99 : 1) (Table 10.9). Moreover, 6 0 -OH-9-amino-9-deoxyepi-quinidine 1r from quinidine was also prepared, and good results were gained while the products had the opposite configuration (entries [16][17][18][19]. Hence, both enantiomers of the cycloaddition products could be readily attainable.…”
Section: Asymmetric Cycloaddition Reactions Catalyzed By Cinchona-basmentioning
confidence: 99%